Delta12-prostaglandin D2 is a potent and selective CRTH2 receptor agonist and causes activation of human eosinophils and Th2 lymphocytes. - Gazi, L; Gyles, S; Rose, J; Lees, S; Allan, C; Xue, L; Jassal, R; Speight, G; Gamble, V; Pettipher, R (2005)
Prostaglandin D2 (PGD2) is a lipid mediator produced by mast cells, macrophages and Th2 lymphocytes and has been detected in high concentrations in the airways of asthmatic patients. There are two receptors for PGD2, namely the D prostanoid (DP) receptor and the chemoattractant receptor-homologous molecule expressed on Th2 cells (CRTH2). The proinflammatory effects of PGD2 leading to recruitment of eosinophils and Th2 lymphocytes into inflamed tissues is thought to be predominantly due to action on CRTH2. Several PGD2 metabolites have been described as potent and selective agonists for CRTH2. In this study we have characterized the activity of delta12-PGD2, a product of PGD2 isomerization by albumin. Delta12-PGD2 induced calcium mobilization in CHO cells expressing human CRTH2 receptor, with efficacy and potency similar to those of PGD2. These effects were blocked by the TP/CRTH2 antagonist ramatroban. delta12-PGD2 bound to CRTH2 receptor with a pKi of 7.63, and a 55-fold selectivity for CRTH2 compared to DP. In Th2 lymphocytes, delta12-PGD2 induced calcium mobilization with high potency and an efficacy similar to that of PGD2. delta12-PGD2 also caused activation of eosinophils as measured by shape change. Taken together, these results show that delta12-PGD2 is a potent and selective agonist for CRTH2 receptor and can cause activation of eosinophils and Th2 lymphocytes. These data also confirm the selective effect of other PGD2 metabolites on CRTH2 and illustrate how the metabolism of PGD2 may influence the pattern of leukocyte infiltration at sites of allergic inflammation.